THE ETYMOLOGY-BASED METHOD OF RECONSTRUCTING SACRAL TEXTS OF HEATHEN SLAVS. THE ORAL TRADITION OF EARLY MEDIEVAL POETRY - Doschek, Jolanta (Prace Polonistyczne, 2021)
In their etymology-based reconstruction of the Proto-Slavic myth of the god Grom and the Serpent god, Vyacheslav Vsevolodich Ivanov and Vladimir Nikolayevich Toporov showed that Slavic folk literature features fragments of Proto-Slavic sacred poetry, which survived in local folklore thanks to oral tradition. The reconstruction method discovered by the Russian scholars helps determine how many elements of ancient phraseology have survived even to this day, mainly thanks to folklore. Radoslav Katičić continues this work and mainly focuses on the folk texts of the Southern Slavs and the Ruthenian folklore, as well as the folklore of other Slavic countries. He searches for traces of another Proto-Slavic myth – that of the Proto-Slavic god of harvest.